Development of Teaching Materials and Harmonized Semester Learning Plan for the Aircraft Basic Workshop Theory Course through Learner-Centered Instructional Design in Indonesian Aviation Polytechnics - Nur, Mulyadi; Sabur, Fatmawati (Newinera Publisher, 2025)
This paper meets the on-going challenge of gaps in the training of Aircraft Basic Workshop Theory course as part of Indonesian aviation polytechnic that seeks to develop an organized competency-based teaching material and integrated RPS (Rencanna Pembelajaran Semester). By using both a Research and Development (R&D) structure borrowed on the 4D model-Define, Design, Develop, and Disseminate and a qualitative (1W) section, the research will combine the validation of stakeholders with the query of the learners to evidence that the pedagogy is relevant and the implementation is possible within the institution. Primary data were collected using the analysis of the curriculum, the consultation of experts, and instrumentation based on the cadets, such as structured questionnaire and semi-structured interviews of Surabaya and Makassar Aviation Polytechnics. Define and Design phase findings showed severe shortage between the formal curriculum requirements and course delivery that involved lack of sequencing of learners; Matching words to learning outcomes and provision of instructional support materials. The created teaching unit and updated RPS has been directly targeting these shortcomings by providing a weekly structure of goals, procedures, and evaluations based on national standards of competencies. At the Disseminate step, the institutional review verified that the instructional tools were usable, adaptable and had systemic worth in various campuses. Above all, acute learner disenfranchisement was identified by the 1W component: cadets claimed that there was a significant level of confusion, the absence of instructional structure, and procedure uncertainty in workshop learning settings.